Hydration Strategies and Their Impact on Physical Performance - A Systematic Review - Kałwa, Natalia; Smerdzyński, Mateusz; Kałuża, Kinga; Pater, Michał; Strzępek, Aleksandra; Łyżwa, Julia; Frączek, Karolina; Janaszek, Agnieszka; Majchrzyk, Aleksandra; Chmurska, Agnieszka (Journal of Education, Health and Sport, 2026)
Adequate hydration is one of the fundamental factors necessary for maintaining physiological homeostasis and optimal physical performance. Disturbances in water-electrolyte balance may occur during physical exercise, when increased fluid loss takes place through sweating and respiratory pathways. Dehydration negatively affects thermoregulatory mechanisms, cardiovascular function and overall exercise capacity. In recent years, hydration strategies have become one of the key areas of research in exercise physiology and sports science. The aim of this systematic review is to analyze the current scientific evidence regarding hydration strategies and their impact on physical performance in athletes and physically active individuals.